2018
DOI: 10.1002/jlb.3ce0418-172r
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine: Therapeutic potential beyond substance abuse

Abstract: Discussion of buprenorphine and its potential utility for the treatment of inflammatory disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Buprenorphine may decrease chronic inflammation ( 23 ). Specifically, one study showed that buprenorphine decreased neuroinflammation in patients with OUD ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…Buprenorphine may decrease chronic inflammation ( 23 ). Specifically, one study showed that buprenorphine decreased neuroinflammation in patients with OUD ( 24 ).…”
Section: Resultsmentioning
confidence: 99%